RESEARCH OF INFLUENCE OF THE IRON CONTENT ON FORMATION OF IRON-BEARING PHASES IN FOUNDRY ALUMINUM ALLOYS - V. I. Gorbachiova; A. V. Terentjeva; M. A. Turchanin; L. A. Dreval (Литьë и металлургия)
The microstructure and microhardness of aluminum and silumin аК12 with iron content of 0 to 12 mas.% produced by sand casting and mol casting have been investigated. For the Al–Si–Fe and Al–Si–Fe–Mn systems the portions of the liquidus surfaces, which correspond to commercial silumin compositions, have been calculated using the updated thermodynamic model of the Al– Si–Fe system and COST–507 database. The area of primary crystallization of the iron-containing a and b phases is assessed for the commercial silumin. It has been proved that manganese promotes the formation of the iron-containing a-phase in the commercial silumin.